Evaluation of a New Patient Record System Using the Optical Card - Brown, J.H.U. (1989)
A new form of patient record has been devised in which a laser imprinted card is coupled to a p.c. for data input and output. Entry of data is simple and recall of any datum requires only a keystroke. Any part of the data can be readily accessed through a software system which encompasses a variety of screens and menus to summarize and combine data. The complete system has been under test in a community health clinic and at NASA and results to date are satisfactory. Preliminary evaluation indicates that the system has no hardware problems, that the software is suitable for the purpose, that patients carry the card and return with it at succeeding visits, that physicians accept that card for a medical record and are pleased with the speed of access and the organization of the data.